An Assessment of Nighttime Electrofishing in the Lower Wabash River. (30th October 2021) - Hine, Eric C.; Colombo, Robert E.; Meiners, Scott J.; Moody‐Carpenter, Cassi J.; Maia, Anabela
Abstract: Large rivers are highly important systems that require close monitoring of the ecological consequences of factors like commercial and recreational exploitation, channel alterations, and climate change. The Long‐Term Survey and Assessment of Large River Fishes in Illinois (LTEF) monitors the fish communities of the Illinois, Mississippi, Wabash, and Ohio rivers using daytime, pulsed‐DC electrofishing between June and October each year. Previous research has documented diel differences in the catch and composition of fish communities. Therefore, the addition of nighttime electrofishing may be beneficial to the overarching goals of long‐term monitoring. This study sought to determine whether there are significant diel differences in fish catch and composition in the Wabash River and whether these potential differences warrant the addition of nighttime sampling to the current protocol. We used nighttime, pulsed‐DC electrofishing at fixed sites corresponding to LTEF sites in the lower Wabash River from June 7 to November 7, 2017. We compared catch per unit effort (CPUE), length distributions, family, and species composition between our nighttime electrofishing data and LTEF daytime electrofishing data. Nonmetric multidimensional scaling showed that the differences between nighttime and daytime electrofishing samples were driven by higher catches of catostomids, centrarchids, and lepisosteids. Nighttime electrofishing had significantly higher mean CPUE than daytime electrofishing, and the four families with significant differences were Catostomidae, Cyprinidae, Lepisosteidae, and Sciaenidae. Of the families for which we compared length data, only Sciaenidae had a significantly different length distribution, with a higher proportional catch of smaller individuals (<100 mm) at night. Despite these differences, compositional shifts were minor, with overlap between daytime and nighttime sampling. Due to the compositional similarities between night and day, the costs of adding nighttime electrofishing to long‐term monitoring would not be necessary. We would recommend nighttime electrofishing for targeting specific taxa and age‐classes that are underrepresented in daytime samples.